Europæisk afhængighed af russisk gas – Har vi noget at frygte? - Nygård, Jakob Riiskjær; Rasmussen, Søren Mollerup (Politik, 2011)
The Russo-Ukranian gas dispute of 2009 has sent ripples through European energy policy debates. Does dependence on Russian gas represent a threat to European energy security via politically motivated supply interruptions? Or was the conflict simply a dispute over the right price of a good? This paper represents a contribution to this debate. Rather than focusing on the outcomes of or motives behind the conflict, we conduct a neoclassical realist analysis of Russian foreign energy policy in order to assess Russia’s ability to use gas as a political instrument of coercion. Our analysis will show that structural conditions promote an increasing emphasis on gas. Furthermore we will show that this shift translates into Russian foreign policy elite consensus about using gas as a foreign policy instrument, and that this consensus is facilitated by an increase in state cohesion since Vladimir Putin assumed the offce of president in 2000.